Effects of Elevated Temperatures on the Growth and Development of Adult Anopheles gambiae (s.l.) (Diptera: Culicidae) Mosquitoes. Issue 4 (22nd April 2022) - Agyekum, Thomas P; Arko-Mensah, John; Botwe, Paul K; Hogarh, Jonathan N; Issah, Ibrahim; Dwomoh, Duah; Billah, Maxwell K; Dadzie, Samuel K; Robins, Thomas G; Fobil, Julius N
Abstract: Higher temperatures expected in a future warmer climate could adversely affect the growth and development of mosquitoes. This study investigated the effects of elevated temperatures on longevity, gonotrophic cycle length, biting rate, fecundity, and body size of Anopheles gambiae (s.l.) (Diptera: Culicidae) mosquitoes. Anopheles gambiae (s.l.) eggs obtained from laboratory established colonies were reared under eight temperature regimes (25, 28, 30, 32, 34, 36, 38, and 40°C), and 80 ± 10% RH. All adults were allowed to feed on a 10% sugar solution soaked in cotton wool; however, some mosquitoes were provided blood meal using guinea pig. Longevity was estimated for both blood-fed and non-blood-fed mosquitoes and analyzed using the Kaplan–Meier survival analysis. One-way ANOVA was used to test the effect of temperature on gonotrophic cycle length, biting rate, and fecundity. Adult measurement data were log-transformed and analyzed using ordinary least square regression with robust standard errors. Increasing temperature significantly decreased the longevity of both blood-fed (Log-rank test; X 2 (4) = 904.15, P < 0.001) and non-blood-fed (Log-rank test; X 2 (4) = 1163.60, P < 0.001) mosquitoes. In addition, the fecundity of mosquitoes decreased significantly (ANOVA; F (2, 57) = 3.46, P = 0.038) with an increase in temperature. Body size (β = 0.14, 95% CI, 0.16, 0.12, P < 0.001) and proboscis length (β = 0.13, 95% CI, 0.17, 0.09, P < 0.001) significantly decreased with increasing temperature from 25 to 34°C. Increased temperatures expected in a future warmer climate could cause some unexpected effects on mosquitoes by directly influencing population dynamics and malaria transmission.